A mouthful of dust - Vo, Nghi (Vo, Nghi. Singing Hills cycle., 2025)
"Hunger makes monsters in this dark new tale in Nghi Vo's Hugo Award-winning Singing Hills Cycle. "Nghi Vo is so good."-NPR on The Brides of High Hill Wandering Cleric Chih of Singing Hills and their hoopoe companion Almost Brilliant come to the river town of Baolin chasing stories of a legendary famine. Amid tales of dishes served to royalty and desserts made of dust, they discover the secrets of what happens when hunger stalks the land and what the powerful will do to hide their crimes. Trapped in the mansion of a sinister magistrate, Chih and Almost Brilliant must learn what happened in Baolin when the famine came to call, and they must do so quickly...because the things in the shadows are only growing hungrier. The Singing Hills Cycle has been shortlisted for the Lambda Literary Award, the Locus Award, and the Ignyte Award, and has won the Crawford Award and the Hugo Award. The novellas are standalone stories linked by the Cleric Chih, and may be read in any order. The Empress of Salt and Fortune When the Tiger Came Down the Mountain Into the Riverlands Mammoths at the Gates The Brides of High Hill A Mouthful of Dust"-- Provided by publisher.